Assessing the performance of takaful companies in Malaysia - Nur'afifah, Abdul Halim (2019)
This research was conducted to assessing the performance of takaful companies in Malaysia. The study attempts to examine the internal factors which are liquidity, equity return, leverage, size of firm, underwriting risk, and external factors; gross domestic product and inflation on performance of takaful company which refer to return on assets. There are reported which are 8 local takaful and 3 foreign takaful were included in the research. Secondary data that was collected in this research comes from the annual financial report (balance sheet and income statements) of takaful companies; and from World Bank Indicator for gross domestic product per capita and consumer price index. The methods employed in this study are Pearson‟s Correlation and Multiple Regression. This research found that the performance of takaful companies was determined by leverage, equity return, underwriting risk and size of firm. However, this research found the external factors does not have significant effect on the performance of takaful companies in Malaysia. This research finding provides financial implications for takaful companies in Malaysia like managing the assets, equity, liability, expenses and etc.